Towards developing Islamic crowdfunding model to harness the potential of students’ entrepreneurial activities in Malaysia - Mohd Thas Thaker, Mohamed Asmy; Duasa, Jarita; Khaliq, Ahmad; Nik Mat, Nik Hziman (Springer, 2025)
The global financial and pandemic crises have worsened the employment challenges faced by university graduates. In order to address this pressing issue, governments are encouraged to utilize “employment pressures” as a mechanism to promote entrepreneurship. By integrating graduate employment with entrepreneurial activities, entrepreneurship can serve as a strategic avenue to generate employment opportunities. Entrepreneurship is a systematic attempt that offers possibilities for creating new ventures and achieving success, with the potential for a multiplier effect that addresses graduate unemployment challenges. In the Malaysian context, while entrepreneurial opportunities are abundant, the lack of entrepreneurial capacity and resilience limits progress. Although university graduates possess advantages such as innovative potential, they face significant barriers, including inadequate access to funding. Islamic crowdfunding emerges as a viable solution to these challenges, offering a model embedded in ethical and societal values. Its focus on generating positive societal impact and supporting graduate entrepreneurial initiatives. This paper seeks to (i) analyze the financing landscape for student entrepreneurship in Malaysia, (ii) propose an innovative financing approach using Islamic crowdfunding, and (iii) establish systematic principles for its implementation. The novelty of the study lies in setting a new research direction for Islamic crowdfunding and financing student’s entrepreneurial activities that can be instrumental in further enhancing and optimizing their potential.